Design and optimization of data center performance - Lim, Melvin Jia Hao. (2012)
Distributed parallel file systems is a storage architecture used in many High Performance Computing (HPC) clusters. With the increasing need to run I/O and data intensive parallel applications in these HPC clusters, there will be a demand for higher processor performance and higher I/O bandwidth from the Distributed file system.